Highly active absorbent for SO2 removal prepared from coal ash (Part 3). - Herrera, A.B.
In the Philippines, the government has started to impose environmental regulations to keep its environment free from hazardous and toxic element. Among the detrimental pollutants being looked into, the government is focusing its attention on the hazardous emissions from coal-fired thermal power plants, in particular, to the reduction of SOx emissions. ITDI has developed a process for the production of highly active absorbents for SOx removal using coal ash and limestone, raw or calcined, as its principal raw materials. In previous studies, the chemical composition, mineral composition, morphological structure and thermal history of coal ash samples were determined to find out their effects on the preparation of the absorbents for SOx removal. Studies on the production of SOx absorbents were conducted and the performance of these absorbents was measured. In this particular paper, the effect of sieving the coal ash samples to obtain most reactive materials will be investigated.